From Formal Hearings to Consequential Oversight: Translating Bovens’s Actor–Forum Accountability Framework for Justice-Sector Oversight - Ligha Nabila Jayasari; Dian Ferriswara; Ika Devy Pramudiana (Discourse Journal on Law and Society, 2026)
Legislative oversight of law-enforcement and judicial institutions must combine democratic answerability with safeguards for legality, independence, due process, confidentiality, and operational integrity. This article examines how Bovens’s actor–forum public accountability framework can illuminate that challenge in the oversight environment of Commission III of the Indonesian House of Representatives. It uses a conceptual review design and a theory-focused narrative literature review with a theory-to-practice orientation. Six documented Scopus search runs produced 1,135 raw records; after removing 132 duplicates, 1,003 unique records were screened. Full text was sought for 60 articles, nine were unavailable, and 51 Scopus-identified journal articles were verified and included. Bovens’s primary framework article was verified separately through citation chaining, producing an analytical corpus of 52 full-text journal articles. Qualitative-interpretive synthesis reconstructed the actor–forum relationship, compared legislative and justice-sector applications, examined accountability deficits, overloads, and boundary conditions, and traced domain formation. The synthesis shows that formal powers, hearings, disclosure, and sanction threats do not by themselves create meaningful accountability. Consequential oversight depends on mandate and role alignment, usable evidence, active and capable forums, traceable follow-up, and proportionate safeguards. These findings are translated into five domains: mandate and role alignment; information and evidence architecture; deliberative scrutiny and forum capability; consequential follow-up and inter-institutional handoffs; and safeguarded accountability. The contribution is conceptual and translational rather than theoretical, and the framework remains a diagnostic guide whose effectiveness requires contextual field validation.